ChemInform Abstract: Catalytic, Formal Homo‐Nazarov‐Type Cyclizations of Alkylidene Cyclopropane‐1, 1‐ketoesters: Access to Functionalized Arenes and Heteroaromatics. Issue 2 (January 2015) - Aponte‐Guzman, Joel; Taylor, J. Evans; Tillman, Elayna; France, Stefan
Abstract The outcome of the title reaction depends on the alkylidene substituents of the substrates.